A description of medicines-related safety issues evaluated through a referral procedure at the EU level after 2012. Issue 6 (2nd June 2020) - Farcas, Andreea; Balcescu, Teodora; Anghel, Laura; Bucsa, Camelia; Mogoșan, Cristina
ABSTRACT: Introduction: Important drug safety issues are evaluated through a referral procedure in the EU by the Pharmacovigilance Risk Assessment Committee (PRAC) within the European Medicines Agency. We aim to describe all safety-related referrals assessed by the PRAC by June 2019. Methods: Publicly available data on safety issues assessed through referral procedures that reached a final decision during July 2012–June 2019 were identified, analyzed and classified according to predefined criteria. Results: Fifty-one safety issues were assessed by PRAC for 45 medicines/combinations/therapeutic classes during this timeframe. Referrals were initiated mostly by the European Commission (16) and France (8). Nine medicines were authorized in the last five years, the rest being well-established drugs. In four cases (flupirtine, hydroxyethyl-starch, valproate, codeine) PRAC re-assessed the same risks as previous recommendations have not been effective. Post-referral recommendations consisted of updates of the summary of product characteristics and package leaflet (42), Direct Healthcare Professional Communication (32), and other additional risk minimization measures (RMMs). Withdrawal was recommended for seven active substances. Conclusions: PRAC recommended routine or additional RMMs for most referrals. Complete withdrawal of a drug or withdrawal of certain pharmaceutical forms or concentrations was advised only when the risk could not be managed by RMMs.